Social Reconfiguration and Marginalization of Farmers in Transmigrant Village in the Context of Coal Industrialization in Tenggarong Seberang, East Kalimantan - Murlianti, Sri; Purwaningsih, Purwaningsih; Hakim, Aji Qamara Dewi; Sriani, Henni; Khusna, Nia Annisyatul; Tabilangi, Charles (Komunitas: International Journal of Indonesian Society and Culture, 2024)
The extractive political economy chosen by the New Oder since the beginning of its rule has transformed natural resource-rich areas in Indonesia into areas at the heart of global capitalism. In the past, extractive politics began by opening the tap for foreign capital to exploit forests, converting scrubland into monoculture plantations and exploiting coal deposits. At the same time, colonial demographic politics were revived to open up major extractive areas, transforming scrubland from former HPH concessions into agricultural areas, alongside coal mining exploration. Tenggarong Seberang District, East Kalimantan has experienced social reconfiguration many times, from an area with a subsistence production model to a major coal extractive area in Kutai Kartanegara Regency. This article describes how Manunggal Jaya Village, which was previously managed by the local farming community, became a center for transmigrant settlements that successfully transformed the village into a center for Kutai rice farming during the New Order era; and drastically changed into a center for supporting services for the multinational mining industry after regional autonomy. The research was conducted for 2 months involving 3 researchers, 2 research assistants throughout August-October 2024. Primary data was collected through observation and in-depth interviews with 10 key informants. The results of the study found a social reconfiguration of the position and role of transmigrant farmers in Tenggarong Seberang. Transmigrants came from poor areas in East Java, became the dominant social class throughout the 1980s-90s, changed drastically into the most vulnerable marginal class entering the mid-2000s. Agricultural land conversion to mining sites, reduced government support; pressures from companies, village bureaucrats, and land brokers have placed significant burdens on farmers. They face water scarcity, land degradation, pollution, new pests, and psychological stress; discouraging younger generations from farming and leaving remaining farmers to struggle under these challenges.